Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Airborne dust particle-induced lung inflammation in mice alleviated by adipose stem cell-derived conditioned medium - Hazrat Zaman; Madiha Habib; Zobia Safdar; Shafi Zaman; Hafiza Sumbul Yousaf; Muhammad Shahbaz Aslam; Zaigham Abbas (Aerobiologia, 2026)

Epitranscriptomic regulation of plant–pathogen interactions and disease resistance - Muhammad Tahir Naseem; Wajid Zaman (Physiological and Molecular Plant Pathology, 2026)

Portable metagenomics for preventive surveillance and outbreak control in livestock and poultry: Pathogen detection, resistome profiling, and antimicrobial stewardship - Muhammad Saeed Akhtar; Wajid Zaman (Research in Veterinary Science, 2026)

Exploring the bioactivity of Ageratum conyzoides L: Antioxidant, antimicrobial, and cytotoxic properties of flower extracts - Md. Safkat Zaman Fahim; Shyama Prosad Moulick; Sauda Sultana Mimi; Subarna Sandhani Dey; Md. Omar Sha Rafi; Sadia Afrin Chhanda; Dabashes Adhikery; Muhammad Mahfuz Hasan; Shahin Aziz; Tanvir Muslim (Next Research, 2026)

Lornoxicam Loaded Transethosomal Gel: Formulation, Box-Behnken Optimization, Ex-Vivo and In-Vivo Characterization - Minahal Munir; Sarah Ahmad; Talha Jamshaid; Huma Hameed; Muhammad Zaman; Usama Jamshaid; Muhammad Jamshaid; Sara Khalid; Heba A. Gad (Journal of Pharmaceutical Innovation, 2026)

Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

Streamflow seasonality responds to changes in snowfall fraction in the Upper Indus Basin - Yixuan Wang; Yan-Jun Shen; Xiaolong Zhang; Muhammad Zaman; Muhammad Imran Khan (Journal of Hydrology, 2026)

Cadmium Nanoparticles Disrupt Root Exosomal Defense Signaling Across Fruit & Root Crops: Mechanisms and Postharvest Rot Susceptibility - Qudrat Ullah; Waqas Haider; Muhammad Waqar; Abdul Rehman; Rashid Abbas Khan; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Plant Molecular Biology Reporter, 2026)

Ti-MOF anchored polyaniline network on separator: A dual-function strategy for polysulfide immobilization and redox enhancement in Li-S batteries - Abdul Majid Khan; Yasir Shah; Fakhar Zaman; Rashida Yahya; Safdar Abbas; Dianfa Zhao; Muhammad Usman Hameed; Wei Liu; Teng Zhang; Zhanpeng Wu (Fuel, 2026)

Retraction notice to “Does communicable diseases (including COVID-19) may increase global poverty risk? A cloud on the horizon” [Environ. Res. 187 (2020) 109668] - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Xuan Vinh Vo; Khalid Zaman (Environmental Research, 2026)

CRISPR-Cas systems for enhancing chilling tolerance in rice: recent advances and future prospects - Muhammad Sikandar Zaman; Asad Azeem; Ayesha Nouman; Abdullah Khalid; Saira Ghafoor; Muhammad Zia Ul Haq; Muhammad Talha Aslam; Hossam S. El-Beltagi (Biologia Futura, 2026)

Eco-friendly tick control using Pakistani bee propolis: Behavioral and acaricidal effects against Rhipicephalus microplus and Hyalomma marginatum - Shahid Nazeer; Shahid Ullah Khan; Shamsheer Khan; Malik Muhammad Sohail Elahi; Syed Ishtiaq Anjum; Khalil ur Rehman; Ruoa Saleh Almahallawi; Amal Abdullah Aboras; Nada Ibrahim Alribdi; Umber Zaman (Veterinary Parasitology, 2026)

Environmental pharmaceutical and antibiotic mixtures: An exposomics-guided framework for mechanistic toxicology - Muhammad Saeed Akhtar; Wajid Zaman (Toxicology Letters, 2026)

Toxicology and biodistribution of plant-derived extracellular vesicles for drug delivery: Quality control, safety mechanisms, and translational testing priorities - Muhammad Tahir Naseem; Wajid Zaman (Toxicology Letters, 2026)

Novel Hybrid Material as a Robust Photocatalyst for Degradation of Aqueous Phenolic Contamination - Bushra Bostan; Saima Sadiq; Inam Ullah; Makkah Zaman; Mian Muhammad; Muhammad Sadiq (Water, Air, & Soil Pollution, 2026)

Multifunctional Greenly Synthesized ZnFe2O4@ZnO Nanocomposites for Photodegradation of Azo Dyes and Antibacterial Applications: Effect of Radical Scavengers and Reaction Parameters - Muhammad Faizan; Muhammad Zahid Ishaque; Yasir Zaman; Abu Bakar Siddique; Muhammad Shahzad; Alia Arif; Hira Zaman (Water, Air, & Soil Pollution, 2026)

Nanoencapsulated EO-based drug delivery for pest control: from chemistry to formulation design - Wajid Zaman; Asma Ayaz; Muhammad Zafar; Adnan Amin (Protoplasma, 2026)

GCMS, phytochemical analysis, biological potential of dichloromethane extract of Yucca elephantipes regel roots: in vitro and in silico studies - Muhammad Shoaib Khan; Mehreen Jabeen; Farhan Siddique; Sajjad Ahmad; Amna Aqdas; Umair Jillani; Yasir Zaman; Abdulrahman Alshammari; Norah A. Albekairi (Natural Product Research, 2026)

In-situ growth of layer double hydroxides on TFC membranes to improve forward osmosis performance - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Woei Jye Lau (Journal of Environmental Chemical Engineering, 2026)

First principles investigation of hafnium-based perovskite hydrides XHfH3 (X: Li, Na, K, and Rb) for hydrogen storage applications - Abdellah Hammad; Djamel Bezzerga; Fouad Keramsi; Ikram Djebablia; Muhammad Zaman; Mamoun Fellah; El-Abed Haidar (Fuel, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Correlating the Performance of Forward Osmosis Process to the Characteristics of Inorganic Draw Solutions - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Niaz Muhammad; Mohamed Shaban; Sameerah I. Al-Saeedi; A. M. Elbasiony; Woei Jye Lau (Water, Air, & Soil Pollution, 2026)

Multi-scale modeling of habitat suitability and human-induced risk for the critically endangered white-rumped vulture (Gyps bengalensis) in South and Southeast Asia - Gulzaman William; Zafeer Saqib; Abdul Qadir; Ayesha Siddiqua; Zaki ul Zaman Asam; Mujahid Farid; Muhammad Jamshed Iqbal Chaudhry (The Science of Nature, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Adaptive role of silicon in enhancing crop resilience and yield under stressful environments: A new window for stress management - Ghulam Murtaza; Muhammad Rizwan; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Rashid Iqbal; Akash Tariq; Gang Deng (Plant Biosystems, 2026)

Human development under environmental and socioeconomic pressures: an ARDL-based assessment of life expectancy in Pakistan - Muhammad Khalid Anser; Muhammad Imran; Helmi Ali Mkaouar; Jameel Ahmad Khader; Alaa Shoukry; Wasfi Yengui; Kamran Azam; Khalid Zaman (Air Quality, Atmosphere & Health, 2026)

Functional, genomic, and transcriptomic insights into linear low-density polyethylene (LLDPE) biodegradation by landfill-derived Brucella intermedia - Ifthikhar Zaman; Mahdi Muhammad Moosa; M. Mahboob Hossain (Journal of Hazardous Materials, 2026)

A comprehensive review on thermo-responsive targeted and functional therapy for management of rheumatoid arthritis - Huma Hameed; Syed Sharf ud Din; Muhammad Zaman; Muhammad Ahsan Waqar; Kainat Fatima; Abdullah Ashraf; Huzaifa Malik; Ahmad Salawi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unveiling Pakistan’s hydro-climatic shifts: trends and change-points in soil moisture and potential evapotranspiration across Pakistan’s climatic zones - Darakshan Naeem; Abdullah Taib; Muhammad Awais; Rizwan Aziz; Muhammad Zaman (Meteorology and Atmospheric Physics, 2026)

Performance evaluation of single and mixed draw solutes in the forward osmosis membrane - B. E. Khan; A. Mahmood; M. Zaman; N. Muhammad; M. Shaban; S. I. Al-Saeedi; A. M. Elbasiony; W. J. Lau (International Journal of Environmental Science and Technology, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Sustainable nanocomposite-integrated polysulfone membranes with tunable surface charge and enhanced adsorptive capacity for heavy metal ions removal from wastewater - Abdullah Arshad; Muhammad Shozab Mehdi; Shafiq Uz Zaman; Saif-ur-Rehman (Chemical Engineering Journal, 2026)

Ferrihydrite-biochar composite for synergistic cadmium immobilization and CH4 emission mitigation in paddy soil - Hangkai Hu; Muhammad Iqbal Zaman; Saiyong Zhu; Jie Hou; Jiang Xu; Kun Yang; Daohui Lin (Journal of Soils and Sediments, 2026)

Technology-society nexus in post-COP 27 era: How digital innovation, energy transition, and green finance drive net-zero pathways in OECD countries - Mubasher Zaman; Atta Ullah; Quande Qin; Muhammad Kashif (Energy Policy, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic effects of biochar and PGPR in enhancing the efficacy of biological control agents against Ganoderma boninense in oil palm (Elaeis guineensis L.): a critical review - Qudrat Ullah; Muhammad Zeshan; Waqas Haider; Muhammad Waqar; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Archives of Microbiology, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Sustainable valorization of leachate at Lakhodair landfill, Lahore: An integrated life cycle environmental and economic assessment of biogas production - Mehak Saghir; Aqsa Ayub; Abdul-Sattar Nizami; Mujtaba Baqar; Hesam Kamyab; Muhammad Waqas; Mohammad Rehan; Zaki-ul-Zaman Asam (Biomass and Bioenergy, 2026)

A Novel Homozygous Loss-of-Function Variant in GPR156 Delineates Non-syndromic Hearing Loss - M. Muaaz Aslam; Safdar Abbas; Shoaib Nawaz; Gohar Zaman; Ishtiaq Ahmed; Misbahuddin Rafeeq; Ziaullah M. Sain; Alaa Hamed Habib; Muhammad Umair; Khadim Shah (Biochemical Genetics, 2026)

Exploring the Links Between Variations in Snow Cover Area and Climatic Variables Across the Upper Indus Basin Under a Changing Climate - Hafsa Muzammal; Muhammad Zaman; Jaehak Jeong; Kashif Mehmood; Syed Aftab Wajid (International Journal of Climatology, 2026)
The Upper Indus Basin (UIB) has experienced gradual changes in water supply due to variations in the Snow Cover Area (SCA) in recent decades. This study examined daily snow cover changes using satellite imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua (2002–2022) and Terra (2001–2022) via Google Earth Engine. An Auto‐regressive Integrated Moving Average (ARIMA) model was developed using time series data to predict SCA. Model accuracy was assessed using Stationarity, ACF, and PACF plots, as well as performance metrics, including AIC, BIC, RMSE, and MSE. The most appropriate iteration (0,1,1) (3,1,1) of the best‐performing model showed strong agreement between observed and simulated SCA, with R 2 values of 0.72 for calibration (2017–2020) and 0.84 for validation (2021–2023). Predicted SCA was further correlated with climate change variables (precipitation, maximum and minimum temperature) from NASA Earth Exchange (NEX) Global Daily Downscaled Projections under SSP1‐2.6 and SSP5‐8.5 scenarios. Results showed a significant decline in SCA, with moderate negative correlations ( r = −0.82 to −0.72) under SSP1‐2.6 and stronger correlations ( r = −0.99 to −0.81) under SSP5‐8.5. Precipitation showed a non‐significant correlation with SCA ( r = 0.14 ± 0.41under SSP1‐2.6; r = 0.11 ± 0.52 under SSP5‐8.5) with decreasing snow cover %. Regionally, Astore, Zanskar, Shigar, and Shingo exhibited significant SCA reductions (tau = −0.585 ± −0.002; p = 0.036 ± p ≤ 0.0001). The Indus_Downstream subbasin showed a non‐significant decreasing trend (tau = −0.002; p = 0.961). These findings highlight the challenges in maintaining runoff, hydropower generation, and freshwater storage, particularly in high‐altitude regions, due to uncertainties in SCA predictions under climate scenarios.

Water quality and pollution dynamics in the Padma River, Bangladesh: Characterization of microbiological and chemical contaminants - Mohammad Kamruzzaman; Md. Nayeem; Mohammad Ismail; Md Firoz Khan; Sharmin Zaman Emon; Anowar Hosen; Asma Rahman; Muhammad Nurul Huda (Regional Studies in Marine Science, 2026)

Diagnosing evaporation in heterogeneous alpine basins using the generalized complementary relationship model integrated with the Budyko framework - Xiaolong Zhang; Yixuan Wang; Yuanyuan Cheng; Muhammad Zaman; Yan-Jun Shen (Journal of Hydrology, 2026)

Modulating LRP1 Pathways in Alzheimer’s Disease: Mechanistic Insights and Emerging Therapies - Tehreem Mushtaq; Huma Hameed; Mahtab Ahmad Khan; Urwa Tariq; Anam Hameed; Muhammad Zaman (Molecular Neurobiology, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Genetic Innovations in Soybean: Key Genes Driving Salinity Tolerance - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Ali Muhammad; Ehsan Ali; Sajjad Ali; Shah Fahad; Xianzhong Feng (Journal of Plant Growth Regulation, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Phytochemical profiling and anticoccidial activity of Syzygium cumini and Trachyspermum ammi extracts against Eimeria zuernii: Integrated in vitro, in vivo, and in silico approaches - Muhammad Zahid Sarfaraz; Sidra Abbas; Muhammad Arfan Zaman; Muhammad Zulqarnain; Kasim Sakran Abass; Asia Parveen; Safina Kousar (Veterinary Parasitology, 2025)

From genes to fields: Genetic determinants and tillage practices shaping cereal root systems for sustainable productivity - Asad Azeem; Sami Ul-Allah; Sana Khan; Muhammad Zia Ul Haq; Muhammad Sikandar Zaman; Syed Ali Murtaza Gallani (Rhizosphere, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Monitoring and optimization of heavy metal phytoextraction in constructed wetlands amended with organic chelators - Mujahid Farid; Ambreen Mussarat; Muhammad Zubair; Zaki ul Zaman Asam; Ayesha Siddiqua; Wajiha Sarfraz; Roha Murtaza; Suliman Mohammed Suliman Alghanem; Haifa Abdul Aziz Sakit Alhaithloul (Environmental Monitoring and Assessment, 2025)

Phytoremediation potential of native tree species for lead removal under domestic wastewater irrigation: a nature-based solution for urban water pollution - Amina Kanwal; Muhammad Farhan; Mehmooda Munazir; Hossam S. El-Beltagi; Qaiser Farid Khan; Qamar uz Zaman; Huma Qureshi; Tauseef Anwar; Wajid Zaman; Dilbar Bazarbayeva; Khairiah Mubarak Alwutayd; Muneera A. Saleh; et al. (Environmental Monitoring and Assessment, 2025)

Submergence stress in plants: molecular mechanisms, physiological changes, and adaptive responses - Noreen Iftikhar; Muhammad Saad Bhutta; Narmeen Tariq Zaman; Ayesha Khalid; Ayesha Latif; Saira Azam; Naila Shahid; Aneela Yasmeen; Abdul Qayyum Rao (Physiology and Molecular Biology of Plants, 2025)

Retraction notice to “Recent advancement challenges with synthesis of biocompatible hemodialysis membranes” [Chemosphere 307, November 2022, 135626] - Shafiq Uz Zaman; Sikander Rafiq; Abulhassan Ali; Muhammad Shozab Mehdi; Amber Arshad; Saif-ur Rehman; Nawshad Muhammad; Muhammad Irfan; Muhammad Shahzad Khurram; Muhammad Khaliq U. Zaman; Abdulkader S. Hanbazazah; Hooi Ren Lim; et al. (Chemosphere, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Corrigendum to: “Substitution of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China” [J Hazard Mater 465 (2024) 1–14 133118] - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2025)

Integration of multivariate indices to correlate pollen morphology and evolutionary adaptations in halophytes - Moona Nazish; Asif Kamal; Muhammad Azhar Khan; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Fozia Bibi; Jawaher Alkahtani; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Potential toxicological assessment of 4-Methylimidazole (4-MEI) in Ctenopharyngodon idella; LC50 determination, acute and sublethal effects on physiological, immunological, and histopathological indicators - Muhib Zaman; Amina Zuberi; Waqar Younas; Muhammad Noorullah; Faisal Ahmad Lodhi; Adnan Khan (Fish Physiology and Biochemistry, 2025)

Levilactobacillus brevis MW362790 and Pediococcus pentosaceus MT323062 Alleviate Cadmium-Induced Oxidative Stress and Hepato-renal Toxicity - Mamoona Hameed; Saman Javed; Najma Arshad; Zaman Gul; Maria Mushtaq; Aneela Munir; Kiran Shazadi; Muhammad Arshad; Saleha Noureen (Current Microbiology, 2025)

Co-location of sheep grazing and solar energy production yields agrotechnological synergies - Nikola Kochendoerfer; A. Sophie Westbrook; Christina E. McMillan; P. Andrew Lapierre; Muhammad A. Zaman; Scott H. Morris; Antonio DiTommaso; Steven M. Grodsky (Agricultural Systems, 2025)

Impact Analysis of Climate Change, Socioeconomic Development, and Hydropower Generation on Water Availability in the Chitral River Basin Using Water Evaluation and Planning (WEAP) Model - Bushra Zaman; Muhammad Atiq Ur Rehman Tariq; Abdullah Nadeem; Muhammad Kaleem Sarwar; Muhammad Waseem; Mudassar Iqbal; Shakeel Hayat; Khalil Ahmed; Muhammad Usman (Water Conservation Science and Engineering, 2025)
Water, energy, and food are three major issues of concern because of the rapid growth of the population and economy, which are exacerbated by climate change. The disparity between the availability and demand of water is largely driven by domestic and agricultural uses, and it is important to evaluate its impact on hydropower generation. This study aims to integrate climate change, socioeconomic development, and hydropower generation analysis using the water evaluation and planning model (WEAP). This study uses the CMIP6 model to make future projections under shared socioeconomic pathways (SSPs). This study examined the projections of water demand under different scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) using the MPI-ESM1-2HR climate change model. In the reference year 2000, domestic water demand stood at 15 MCM, escalating to 54 MCM under the SSP5-8.5 scenario. Concurrently, agricultural water demand, which was 93.72 MCM in 2000, is projected to surge to 197.35 MCM by 2050. Based on expected future changes in streamflow, the results show that Golen Gol’s hydropower potential varies with the effects of socioeconomic and climatic changes. However, the fluctuation in hydropower generation is more prominent during June and July, leading to an increase in hydropower in future scenarios. The study findings suggest that by 2050, the combination of population growth and agricultural expansion will substantially escalate water demand, posing risks to both the environment and human populations. Consequently, adopting enhanced irrigation methods, refining agricultural techniques, and erecting water conservation and retention infrastructures could effectively mitigate these challenges. To formulate sustainable water management strategies, it is advised to further utilize the integrated water–energy–food nexus approach, strengthened by merging WEAP with the energy modeling program Low Emissions Analysis Platform (LEAP) for hydropower generation.

Potential beneficial effects of dietary replacement of fish meal with Black soldier fly (Hermetia illucens) larvae meal on growth, general physiology, and microanatomy of Nile tilapia (Oreochromis niloticus) - Waqar Younas; Amina Zuberi; Faisal Ahmad Lodhi; Muhib Zaman; Muhammad Noorullah; Muhammad Ali (Fish Physiology and Biochemistry, 2025)

Challenges and Strategies in Managing Naegleria fowleri-Associated Primary Amoebic Meningoencephalitis in Pakistan: A Case Report - Maham Zaman; Tooba Fida; Hafiz Muhammad Haris; Zarmeen Naveed; Shaheer Haider; Tauqeer Khan (Acta Parasitologica, 2025)

Comparative efficacy of imidocarb dipropionate with additive in naturally infected cattle against bovine babesiosis - Sajida Bibi; Sidra Abbas; Muhammad Arfan Zaman; Roquyya Gul; Aima Iram Batool; Iqra Khalil; Arbab Sikandar; Farhan Ahmad Atif (Veterinary Parasitology, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Urban energy efficiency in China: Examining the role of renewable energy, smart Grids, and sustainable design through spatial and policy perspectives (1990–2022) - Muhammad Khalid Anser; Faiza Sajjad; Abdelmohsen A. Nassani; Khalid M. Al-Aiban; Khalid Zaman; Mohamed Haffar (Energy and Buildings, 2025)

Geo-spatial distribution of air pollutants in urban area and its potential health risk analysis solutions - Fajar Waheed; Nusrat Ehsan; Rabiya Nasir; Waqas Ahmed Khan; Muhammad Fahim Khokhar; Laila Shahzad; Aqil Tariq; Hira Afzal; Qamar uz Zaman (Urban Climate, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Pollen patterns and morphological variability unraveling taxonomic relevance and evolutionary relationship in salt-tolerant species - Moona Nazish; Asif Kamal; Muhammad Zafar; Mushtaq Ahmad; Ghulam Mujtaba Shah; Jawaher Alkahtani; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Muhammad Tahir Naseem; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

A Potent Plant-Derived Chitinase: Structural Informatics and Insecticidal Activity against Helicoverpa armigera - Shah Rukh; Ahmed Akrem; Qamar Saeed; Sohaib Mehmood; Nosherwan Adil; Tazeen Rao; Muhammad Nasir; Uzma Ishaq; Aqal Zaman; Najeeb Ullah; Mohibullah Shah (Cell Biochemistry and Biophysics, 2025)

Exogenous applications of humic acid and salicylic acid differentially affect biomass accumulation and production of rare pharmacologically active withanolides in in vitro cultures of Withania coagulans - Mehnaz Khanum; Muhammad Uzair Javed; Sannia Batool; Gouhar Zaman; Muhammad Naeem Bajwa; Anisa Andleeb; Laurine Garros; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2025)

Exploring melatonin’s influence on secondary metabolism of Echinacea purpurea callus cultures - Tehreem Mahmood; Muhammad Uzair Javed; Gouhar Zaman; Bushra Khan; Negin Zarei; Cécile Abdallah; Christophe Hano; Johan-Owen De Craene; Arnaud Lanoue; Bilal Haider Abbasi; Nathalie Giglioli-Guivarc’h (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Role of plant growth-promoting rhizobacteria in sustainable agriculture: Addressing environmental and biological challenges - Abdul Wahab; Farwa Batool; Gholamreza Abdi; Murad Muhammad; Shahid Ullah; Wajid Zaman (Journal of Plant Physiology, 2025)

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Recovery, modifications, physicochemical properties, and MB removal efficiency of marble waste powder - Najm Us Saqib; Jamshid Abbas; Imran Ullah; Muhammad Abdul Haleem; Asma Aamir; Falak Zaman; Irfan Ullah (Environmental Science and Pollution Research, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Development of a dispersive liquid–liquid microextraction technique for ultra-sensitive detection of gold in environmental samples using atomic absorption spectrometry - Waheed Ali Soomro; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani; Zulfiqar Ali Bhatti; Rafi-u-Zaman Brohi; Imran Khan Rind (Environmental Monitoring and Assessment, 2025)

Peptide-based vaccine design against Hendra virus through immunoinformatics approach - Asifa Sarfraz; Irfa Chaudhary; Fizza Arshad; Muhammad Shehroz; Asia Perveen; Umar Nishan; Abid Ali; Riaz Ullah; Abdelaaty A. Shahat; Aqal Zaman; Mohibullah Shah (Veterinary Immunology and Immunopathology, 2025)

Enhancing phytoremediation in chamomile (Matricaria chamomilla L.) using moringa extract and zero-valent iron nanoparticles - Urooj Ansar Mughal; Mujahid Farid; Wajiha Sarfraz; Mostafa A. Abdel-Maksoud; Abdul Malik; Zaki ul Zaman Asam; Mohsin Abbas; Muhammad Zubair; Sabiha Fatima; Noreen Khalid (South African Journal of Botany, 2025)

De Novo synthesis of selenium-doped CeO2@Fe3O4 nanoparticles for improving secondary metabolite biosynthesis in Carthamus tinctorius cell suspension culture - Kamran Ashraf; Zebo Liu; Qamar uz Zaman; Muhammad Arshad; Waqas Qamar Zaman; Ali Shan; Junxiong Yu; Touseef ur Rehman; Yingping Zhuang; Meijin Guo; Ali Mohsin (Chemical Engineering Journal, 2025)

Computer-aided rational design of a mRNA vaccine against Guanarito mammarenavirus - Mohibullah Shah; Asifa Sarfraz; Muhammad Shehroz; Asia Perveen; Samavia Jaan; Aqal Zaman; Umar Nishan; Arlindo A. Moura; Riaz Ullah; Zafar Iqbal; Mohamed A. Ibrahim (Biotechnology Letters, 2025)

The role of agricultural land management in modulating water-carbon interplay within dryland ecological systems - Wajid Ali Khattak; Jianfan Sun; Fawad Zaman; Abdul Jalal; Muhammad Shafiq; Sehrish Manan; Rashida Hameed; Ihtisham Khan; Irfan Ullah Khan; Khalid Ali Khan; Daolin Du (Agriculture, Ecosystems & Environment, 2025)

GIS-based spatial assessment of water quality, soil, and plant: a case study of Darawat Dam Sindh, Pakistan - Muhammad Farooque Lanjwani; Muhammad Yar Khuhawar; Rafi-O.-zaman Brohi; Waheed Ali Soomro; Abdul Hameed Lanjwani; Muhammad Umar Lanjwani (Environmental Monitoring and Assessment, 2025)

Toxicity and fitness evaluation of Chrysoperla carnea resistant strains on cotton mealy bug Phenacoccus solenopsis Tinsely - Mashahood Ali Khan; Sarfraz Ali Shad; Fehmina Atta; Muhammad Gul Zaman; Muhammad Abubakar (Crop Protection, 2025)

Maackiain: A comprehensive review of its pharmacology, synthesis, pharmacokinetics and toxicity - Waqas Haider; Wei Pan; Dayang Wang; Waqas Niaz; Muhammad Kashif Zaman; Raza Ullah; Shakir Ullah; Muhammad Rafiq; Bing Yu; Hailin Cong (Chemico-Biological Interactions, 2025)

Mitigation of salinity stress in sunflower plants (Helianthus annuus L.) through topical application of salicylic acid and silver nanoparticles - Muhammad Shahbaz; Tauseef Anwar; Sammer Fatima; Nilgün Onursal; Huma Qureshi; Waseem Akhtar Qureshi; Naimat Ullah; Walid Soufan; Wajid Zaman (Physiology and Molecular Biology of Plants, 2025)

Pollution level assessment, source apportionment, and health hazards of heavy metals and rare earth elements in the sediment core from the coast of Karachi, Pakistan - Naila Siddique; Muhammad Zaman Chaudhary; Mavia Anjum; Jawaria Abid (Marine Pollution Bulletin, 2024)

Effect of differential exposure of UV-C and melatonin stress on the therapeutic potential of bioactive compounds in Moringa oleifera - Muhammad Naeem Bajwa; Gouhar Zaman; Muhammad Asad Ullah; Muhammad Uzair Javed; Anisa Andleeb; Christophe Hano; Bilal Haider Abbasi (South African Journal of Botany, 2024)

The pivotal role of arbuscular mycorrhizal fungi in enhancing plant biomass and nutrient availability under drought stress conditions: A global meta-analysis - Fawad Zaman; Muhammad Umair Hassan; Wajid Ali Khattak; Ahmad Ali; Mohamed F. Awad; Fu-Sheng Chen (Science of The Total Environment, 2024)

Spatio-temporal human snow leopard (Panthera uncia) conflicts and mitigation measures in Baltistan - free-livestock grazing pastoral areas - Muhammad Zaman; Rodney Jackson; Shafqat Hussain (Journal for Nature Conservation, 2024)

Food safety profile of university food handlers in Bangladesh: A multicenter cross-sectional study - Tahsin Ahmed Rupok; Shahnaz Parvin Sweety; Mst. Mahfuza Rahman; Most. Tasfia Rahman; Fahmida Zaman; Muhammad Radone Ahmed; Tanvirul Islam; Md. Nurnobi Islam; Md. Masud Rana; Abdur Rahman Riaz; Md. Golam Sadik (Food and Humanity, 2024)

Kinetics of silver ion encapsulation as nanoparticles using Vaccinium oxycoccos plant extract for the efficient sensing of Cr(iii) ions and its biological assessment - Amna Bibi; Muhammad Iqbal Zaman; Abdul Niaz; Sania Bibi; Saba Gul; Naveed Ahmad; Hanan E. Osman (Chemical Engineering Journal, 2024)

The potential of biochar incorporation into agricultural soils to promote sustainable agriculture: insights from soil health, crop productivity, greenhouse gas emission mitigation and feasibility perspectives—a critical review - Muhammad Saif Ullah; Raheleh Malekian; Gurjit S. Randhawa; Yuvraj Sing Gill; Sundeep Singh; Travis J. Esau; Qamar U. Zaman; Hassan Afzaal; Dao Lin Du; Aitazaz A. Farooque (Reviews in Environmental Science and Bio/Technology, 2024)

Sequence variants underlying severe combined immunodeficiency and leukocyte adhesion deficiency type 1 in six consanguineous families - Hajra Fayyaz; Atteaya Zaman; Nighat Haider; Rehmana Waris; Muhammad Hussain; Syed Irfan Raza; Wasim Ahmad; Imran Ullah (Immunogenetics, 2024)

Comprehensive insights on treatment modalities with conventional and herbal drugs for the treatment of duodenal ulcers - Huma Hameed; Jahangir Hussain; Ana Cláudia Paiva-Santos; Muhammad Zaman; Ali Hamza; Irsa Sajjad; Faria Asad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Photocatalytic hydrogen peroxide production: Advances, mechanistic insights, and emerging challenges - Shahid Khan; Muhammad Adnan Qaiser; Waqar Ahmad Qureshi; Syed Najeeb-uz-Zaman Haider; Xiaohui Yu; Weikang Wang; Qinqin Liu (Journal of Environmental Chemical Engineering, 2024)

CFD modelling of a chemical looping combustion system − Exploring the potential of natural oxygen carriers - Fazal e Rabbi; Atta Ullah; Aitazaz Hassan; Muhammad Zaman; Liang Zeng; Feng Xin (Fuel, 2024)

Feasible biosynthesis of biologically active metabolites in in vitro culture of Macrotyloma uniflorum - Sannia Batool; Mehnaz Khanum; Hasnat Tariq; Gouhar Zaman; Muhammad Uzair Javed; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc'h (Biocatalysis and Agricultural Biotechnology, 2024)

Exploring the potential of nanomedicine for gene therapy across the physicochemical and cellular barriers - Huma Hameed; Hafiz Shoaib Sarwar; Komel Younas; Muhammad Zaman; Muhammad Jamshaid; Ali Irfan; Maha Khalid; Muhammad Farhan Sohail (Functional & Integrative Genomics, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

A potential toxicological risk assessment of heavy metals and pesticides in irrigated rice cultivars near industrial areas of Dhaka, Bangladesh - Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Anowar Hosen; Mahafuga Akter; Md. Mominul Islam; Sharmin Zaman Emon; Asma Rahman; Zuairia Binte Jashim; Saif Shahrukh; Mohammad Ismail (Environmental Monitoring and Assessment, 2024)

Vermi-remediation impacts on growth and metals bioaccumulation in tomato irrigated with wastewater - Mehboob Alam; Anwarzeb Khan; Rasheeqa Zaman; Shahnawaz Khan; Muhammad Amjad Khan; Imran Ahmad; Abdullah Jalal; Ki In Kim (Chemosphere, 2024)

Insights in to iron-based nanoparticles (hematite and magnetite) improving the maize growth (Zea mays L.) and iron nutrition with low environmental impacts - Nauman Yousaf; Muhammad Fahad Sardar; Muhammad Ishfaq; Baogang Yu; Yanting Zhong; Faisal Zaman; Fusuo Zhang; Chunqin Zou (Chemosphere, 2024)

Differential expression and bioinformatics analysis of proteins in response to NaCl stress in purslane - Hongmei Du; Shah Zaman; Fiza Liaquat; Shuiqingqing Hu; Muhammad Farooq Hussain Munis; Shengquan Che (South African Journal of Botany, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Phytochemical-mediated regulation of aflatoxigenic fungi contamination in a shifting climate and environment - Shah Zaman; Nasrullah Khan; Muhammad Zahoor; Riaz Ullah; Ahmed Bari; Sohail (Environmental Geochemistry and Health, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Techno-economic analysis of small-scale ammonia production via sorption-enhanced gasification of biomass - Godknows Dziva; Chuanbao Luan; Guangchao Ding; Abdoulaye Boré; Kouame Jean Ives Kouakou; Tinashe Tembo; Atta Ullah; Muhammad Zaman; Songgeng Li; Liang Zeng (Chemical Engineering Journal, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Qualitative and quantitative analysis of high-value metabolites from callus culture of Alcea rosea L. - Hasnat Tariq; Anisa Andleeb; Sannia Batool; Urooj Ali; Muhammad Waqas; Abdul Wahab; Gouhar Zaman; Samantha Drouet; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Detailed sedimentological investigation of the late cretaceous fort munro formation, western sulaiman range, Pakistan - Badar U Zaman; Mohibullah Mohibullah; Razzaq Abdul Manan; Akhtar Muhammad Kassi; Muhammad Rizwan (Carbonates and Evaporites, 2024)

Tourism triumphs: unraveling the essence of Asia’s allure through governance, FDI, and natural bounties - Muhammad Zaheer Akhtar; Khalid Zaman; Muhammad Azhar Khan (Journal of Environmental Studies and Sciences, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

RETRACTED ARTICLE: Multifaceted role of TRIM21 in inflammation - Sana Tanveer; Ali Afzal; Zaman Gul; Hanan Afzal; Amara Noureen; Muhammad Sharif; Muhammad Babar Khawar (Biologia Futura, 2024)

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Assessing the health risks of heavy metals and seasonal minerals fluctuations in Camellia sinensis cultivars during their growth seasons - Fawad Zaman; Wajid Ali Khattak; Muhammad Ihtisham; Muhammad Ilyas; Ahmad Ali; Abbas Ali; Haroon Khan; Khalid Ali Khan; Dejiang Ni; Hua Zhao; Fu-Sheng Chen (Food and Chemical Toxicology, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

From field to table: Ensuring food safety by reducing pesticide residues in food - Salman Munir; Asad Azeem; Muhammad Sikandar Zaman; Muhammad Zia Ul Haq (Science of The Total Environment, 2024)

Contaminant transport from solid waste dumps: Implications for environmental degradation with a focus on capital territory regions - Muhammad Naeem; Zaki ul Zaman Asam (Environmental Research, 2024)

Reduced toxic effects of nano‑copper sulfate in comparison of bulk CuSO4 on biochemical parameters in the Rohu (Labeo rohita) - Azka Anwar; Fahim Ullah Khan; Waqar Younas; Muhib Zaman; Muhammad Noorullah; Li'ang Li; Amina Zuberi; Youji Wang (Toxicology in Vitro, 2024)

Substation of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2024)

Evaluating the U-shaped environmental kuznets curve in China: The impact of high technology exports and renewable energy consumption on carbon emissions - Meng Shang; Michael Yao-Ping Peng; Muhammad Khalid Anser; Muhammad Imran; Abdelmohsen A. Nassani; Rima H. Binsaeed; Khalid Zaman (Gondwana Research, 2024)

Physiological and histopathological effects of polystyrene nanoparticles on the filter-feeding fish Hypophthalmichthys molitrix - Muhib Zaman; Fahim Ullah Khan; Waqar Younas; Muhammad Noorullah; Imdad Ullah; Li’ang Li; Amina Zuberi; Youji Wang (Science of The Total Environment, 2024)

Zinc sulfate as a draw solute in forward osmosis and its regeneration by reagent precipitation - Bilal Ejaz Khan; Asif Mahmood; Muhammad Zaman; Kew-Ho Lee (Desalination, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Enhancement in the production of phenolic compounds from Fagonia indica callus cultures via Fusarium oxysporum triggered elicitation - Taimoor Khan; Muhammad Uzair Javed; Tehreem Mahmood; Bushra Khan; Tariq Khan; Muhammad Asad Ullah; Razia Khurshid; Gouhar Zaman; Christophe Hano; Nathalie Giglioli-Guivarc’h; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2024)

Therapeutic Physical Properties, Photocatalytic, and Anti-bacterial Activities of Hydrothermally Fabricated Cu-doped ZnO NPs - Muhammad Zahid Ishaque; Yasir Zaman; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Hira Zaman; Sarmad Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Radon concentration in spring water as an indicator of seismic activity: a case study of the Muzaffarabad Fault in Pakistan - Sayed Qamar Abbas; Jahanzeb Khan; Muhammad Tayyib Riaz; Muhammad Rafique; Ali Zaman; Sajjad Khan (Environmental Monitoring and Assessment, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Coffee authentication via targeted metabolomics and machine learning: Unveiling origins and their discriminating biochemicals - Fawzan Sigma Aurum; Muhammad Zukhrufuz Zaman; Edi Purwanto; Danar Praseptiangga; Kohei Nakano (Food Bioscience, 2023)

Colorimetric detection of phosphate-based on iron complexing catechol-displacement assay in eutrophicated water bodies - Rafaqat Naveen; Abdul Niaz; Muhammad Iqbal Zaman; Shahanzeb Khan; Abdur Rahim; Asma Zulfiqar; Muhammad Tariq; Tawfik. A. Saleh; Diogo M. F. Santos; Mabkhoot Alsaiari (Environmental Nanotechnology, Monitoring & Management, 2023)

Transparency enhancement of supply chain capabilities through social media: a proposed hierarchical model - Sharfuddin Ahmed Khan; Muhammad Shujaat Mubarik; Syed Imran Zaman; Alessio Ishizaka; Kanwal Saleem (Environment, Development and Sustainability, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Alleviation of cadmium toxicity and fortification of zinc in wheat cultivars cultivated in Cd contaminated soil - Khadim Dawar; Ishaq Ahmad Mian; Shadman Khan; Anwar Zaman; Subhan Danish; Ke Liu; Matthew Tom Harrison; Shah Saud; Shah Hassan; Taufiq Nawaz; Imran Khan; Haitao Liu; et al. (South African Journal of Botany, 2023)

Methyl jasmonate and iron oxide nanoparticles act as elicitors to stimulate production of bioactive antioxidants and metabolites in the in vitro callus cultures of Bergenia ciliata (haw.) Sternb - Tauqeer Sardar; Muhammad Ishtiaq; Muhammad Waqas Mazhar; Mehwish Maqbool; Ihab Mohamed Moussa; Wajid Zaman; Eman A. Mahmoud (South African Journal of Botany, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Anxiolytic-like effect of succinic acid: A possible GABAergic intervention - Md. Nayem Mia; Shanita Zaman Smrity; Mehedi Hasan Bappi; Hossam Kamli; Tawhida Islam; Abdullah Al Shamsh Prottay; Md. Showkoth Akbor; Md. Abdul Latif; Shoriful Islam; Kushal Bhakta; Manik Chandra Shill; Francisco Claudeni Pereira de Sousa; et al. (Food Bioscience, 2023)

Bifunctional photothermal membrane for high-temperature interfacial solar steam generation and off-grid sterilization - Laila Noureen; Shahid Zaman; Waqas Ali Shah; Qian Wang; Muhammad Humayun; Qiyong Xu; Xinwei Wang (Chemical Engineering Journal, 2023)

Introducing two new members of the genus Candolleomyces (Agaricales, Psathyrellaceae) from Punjab, Pakistan - Aiman Izhar; Muhammad Asif; Zaman Khan; Abdul Nasir Khalid (Plant Systematics and Evolution, 2023)

Assessment of radiological indices and physiochemical characterization of sediments in Chashma Lake, Pakistan - Mustafa Khan; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Jawaria Abid; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2023)

Heterologous expression of bacterial dehydrin gene in Arabidopsis thaliana promotes abiotic stress tolerance - Nadir Zaman Khan; Akhtar Ali; Waqar Ali; Muhammad Aasim; Tariq Khan; Zaryab Khan; Iqbal Munir (Physiology and Molecular Biology of Plants, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

The influence of exogenous melatonin and chitosan on secondary metabolites’ production and biological activities of tissue extracts in agitated micro-shoot cultures of Ajuga integrifolia Buch. Ham. ex D.Don - Muhammad Asad Ullah; Faiza Zareen Gul; Gouhar Zaman; Junaid Iqbal; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi (Acta Physiologiae Plantarum, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Exploring the nexus between green innovations and green growth in G-7 economies: evidence from wavelet quantile correlation and continuous wavelet transform causality methods - Umer Zaman; Muhammad Zubair Chishti; Touseef Hameed; Muhammad Sohail Akhtar (Environmental Science and Pollution Research, 2023)

Isolation of two new triterpene glycoside from the fruits of Terminalia arjuna and their in vitro and in silico studies - Rashadul Hossain; Rajia Sultana; Md. Din Islam; Shahed Zaman; Muhammad Iqbal Choudhary (Natural Product Research, 2023)

The role of carbon pricing in the relationship between air freight and environmental resource depletion: a case study of Saudi Arabia - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Clean Technologies and Environmental Policy, 2023)

Effects of the circular economy, environmental policy, energy transition, and geopolitical risk on sustainable electricity generation - Muhammad Zubair Chishti; Eyup Dogan; Umer Zaman (Utilities Policy, 2023)

MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation - Nurul Syazana Fuzil; Nur Hidayati Othman; Nur Hashimah Alias; Fauziah Marpani; Muhammad Shafiq Mat Shayuti; Munawar Zaman Shahruddin; Mohd Rizuan Mohd Razlan; Norazah Abd Rahman; Woei Jye Lau; Mohd Hafiz Dzarfan Othman; Ahmad Fauzi Ismail; Tutuk Djoko Kusworo; et al. (Journal of Environmental Chemical Engineering, 2023)

Evaluating powder preparation of Dodonaea viscosa as a new potential control measure against bacterial wilt of tomato - Kashif Ahmad; Raja Asad Ali Khan; Musharaf Ahmad; Rizwan Khan; Ishrat Naz; Saeed Ullah; Waleed Khan; Muhammad Waleed; Shahab Khan; Asad Zaman (Journal of Plant Pathology, 2023)

Access to sustainable healthcare infrastructure: a review of industrial emissions, coal fires, and particulate matter - Muhammad Imran; Shiraz Khan; Abdelmohsen A. Nassani; Mohamed Haffar; Haroon ur Rashid Khan; Khalid Zaman (Environmental Science and Pollution Research, 2023)

Navigating the global mineral market: A study of resource wealth and the energy transition - Donglei Yu; Xiong Wenhui; Muhammad Khalid Anser; Abdelmohsen A. Nassani; Muhammad Imran; Khalid Zaman; Mohamed Haffar (Resources Policy, 2023)

Enhancing carbon capture efficiency of zeolite-embedded polyether sulfone mixed-matrix membranes via annealing process - Aamir Sohail; Muhammad Sarfraz; Sidra Nawaz; Zaman Tahir (Journal of Cleaner Production, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

Efficacy of marigold (Tagetes erecta L.) for the treatment of tannery and surgical industry wastewater under citric acid amendment: a lab scale study - Arooj Fatima; Mujahid Farid; Zaki Ul Zaman Asam; Muhammad Zubair; Sheharyaar Farid; Mohsin Abbas; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Exogenous Selenium as a Potent Modulator of Antioxidants, Osmo-protectants, Lipid Peroxidation, and Wheat Grain Yield Under Terminal Heat Stress - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Haroon Zaman Khan (Journal of Soil Science and Plant Nutrition, 2022)

Impact of Probiotic Geotrichum candidum QAUGC01 on Health, Productivity, and Gut Microbial Diversity of Dairy Cattle - Shahid Zaman; Madeeha Gohar; Hafsa Kanwal; Afia Chaudhary; Muhammad Imran (Current Microbiology, 2022)

Assessment of Climate Change and Its Impacts on the Flows of a Subtropical River Basin in the Hindu-Kush Mountain, South Asia - Muhammad Naveed Anjum; Abdulnoor A. J. Ghanim; Hafiz Umar Farid; Muhammad Zaman; Usama Muhammad Niazi; Saif ur Rahman; Mabkhoot A. Alsaiari; Muhammad Irfan (Pure and Applied Geophysics, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Catalytic potential of endophytes facilitates synthesis of biometallic zinc oxide nanoparticles for agricultural application - Saddam Saqib; Amna Nazeer; Muhammad Ali; Wajid Zaman; Muhammad Younas; Asim Shahzad; Sunera; Momina Nisar (BioMetals, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Evaluating race-to-the-top/bottom hypothesis in high-income countries: controlling emissions cap trading, inbound FDI, renewable energy demand, and trade openness - Bibi Aisha Sadiqa; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Do affluent nations value a clean environment and preserve it? Evaluating the N-shaped environmental Kuznets curve - Fiza Shaheen; Khalid Zaman; Muhammad Saeed Lodhi; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Phosphate solubilizing epilithic and endolithic bacteria isolated from clastic sedimentary rocks, Murree lower Himalaya, Pakistan - Imran Khan; Sahib Zada; Muhammad Rafiq; Wasim Sajjad; Sumayya Zaman; Fariha Hasan (Archives of Microbiology, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Assessment of contaminants in sand production from petroleum wells offshore Sabah - Muhammad Shafiq Mat Shayuti; Suzalina Zainal; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Munawar Zaman Shahruddin; Nur Hidayati Othman; Nur Hashimah Alias; Tengku Amran Tengku Mohd; Rahida Wati Sharudin (Environmental Science and Pollution Research, 2022)

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Effects of Ferula asafetida, closantel, albendazole, oxfendazole, and ivermectin against Haemonchus contortus in goats and sheep - Abdul Jabbar; Muhammad Zahid Iqbal; Muhammad Ashraf; Aneela Zameer Durrani; Hira Sajjad; Mohammed Nasiru Wana; Asad Ullah; Muhammad Imran; Muhammad Shair Zaman Ghauri; Hafiz Ishfaq Ahmad (Tropical Animal Health and Production, 2022)

Evaluating pollution damage function through carbon pricing, renewable energy demand, and cleaner technologies in China: blue versus green economy - Muhammad Zaheer Akhtar; Khalid Zaman; Faheem Ur Rehman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Identification of putative genetic variants in major depressive disorder patients in Pakistan - Sarah Rizwan Qazi; Muhammad Irfan; Zoobia Ramzan; Muhammad Jahanzaib; Maleeha Zaman Khan; Mahrukh Nasir; Muhammad Shakeel; Ishtiaq Ahmad Khan (Molecular Biology Reports, 2022)

Do environmental pollutants carrier to COVID-19 pandemic? A cross-sectional analysis - Salman Shamsi; Khalid Zaman; Bushra Usman; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Radiological risk assessment in sediment of Namal Lake, Mianwali, Pakistan - Irfan Afzal; Muhammad Zaman Chaudhary; Ehsan Ullah Khan; Tabassum Nasir; Nadeem Yaqoob (Environmental Monitoring and Assessment, 2022)

Structural characterization and antileishmanial activity of newly synthesized organo-bismuth(V) carboxylates: experimental and molecular docking studies - Sohaila Andleeb; Imtiaz-ud-Din; Muhammad Khawar Rauf; Syed Sikander Azam; Ihsan‐ul Haq; Muhammad Nawaz Tahir; Naila Zaman (JBIC Journal of Biological Inorganic Chemistry, 2022)

Environmental and natural resource degradation in the wake of COVID-19 pandemic: a wake-up call - Muhammad Khalid Anser; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Nonlinearity in the relationship between COVID-19 cases and carbon damages: controlling financial development, green energy, and R&D expenditures for shared prosperity - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Hailan Salamun; Sasmoko; Yasinta Indrianti; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

The impact of coal combustion, nitrous oxide emissions, and traffic emissions on COVID-19 cases: a Markov-switching approach - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

The mediating role of ICTs in the relationship between international tourism and environmental degradation: fit as a fiddle - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Iron-doped zinc oxide nanoparticles-triggered elicitation of important phenolic compounds in cell cultures of Fagonia indica - Atta Ullah Khan; Tariq Khan; Mubarak Ali Khan; Akhtar Nadhman; Muhammad Aasim; Nadir Zaman Khan; Waqar Ali; Nausheen Nazir; Muhammad Zahoor (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Socio-economic and corporate factors and COVID-19 pandemic: a wake-up call - Muhammad Khalid Anser; Sheikh Usman Yousaf; Shabir Hyder; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

Financial development, oil resources, and environmental degradation in pandemic recession: to go down in flames - Muhammad Khalid Anser; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Does COVID-19 pandemic disrupt sustainable supply chain process? Covering some new global facts - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Does improvement in the environmental sustainability rating help to reduce the COVID-19 cases? Controlling financial development, price level and carbon damages - Muhammad Khalid Anser; Bushra Usman; Shabir Hyder; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Short targeting multiplex PCR assay to detect and discriminate beef, buffalo, chicken, duck, goat, sheep and pork DNA in food products - Syed Muhammad Kamal Uddin; M. A. Motalib Hossain; Zaira Zaman Chowdhury; Mohd Rafie Bin Johan (Food Additives & Contaminants: Part A, 2021)

Achieving pro-poor growth and environmental sustainability agenda through information technologies: as right as rain - Muhammad Imran; Khan Burhan Khan; Khalid Zaman; Mohammed Borhandden Musah; Elih Sudiapermana; Abdul Rashid Abdul Aziz; Rahimah Embong; Zainudin Bin Hassan; Mohd Khata Jabor; Siti Nisrin Mohd Anis (Environmental Science and Pollution Research, 2021)

Progress in nuclear energy with carbon pricing to achieve environmental sustainability agenda: on the edge of one’s seat - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Demographic, psychological, and environmental factors affecting student’s health during the COVID-19 pandemic: on the rocks - Muhammad Khalid Anser; Muhammad Sharif; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

The role of information and communication technologies in mitigating carbon emissions: evidence from panel quantile regression - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Mechanism and role of seeded native grasses to immobilize nitrogen on harvested blanket peat forests for protection of water courses - Zaki-ul-Zaman Asam; Connie O’Driscoll; Mohsin Abbas; Mark O’Connor; Muhammad Waqas; Mohammad Rehan; Abdul-Sattar Nizami; Liwen Xiao (Environmental Science and Pollution Research, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Heat-related illnesses in a mass gathering event and the necessity for newer diagnostic criteria: a field study - Wesam Alkassas; Ahmad Mamoun Rajab; Sara T. Alrashood; Muhammad Ayub Khan; Mahmoud Dibas; Mohsin Zaman (Environmental Science and Pollution Research, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Antibiofilm Effects of Macrolide Loaded Microneedle Patches: Prospects in Healing Infected Wounds - Muhammad Sohail Arshad; Aleema Tehreem Zahra; Saman Zafar; Hussain Zaman; Ambreen Akhtar; Muhammad Mazhar Ayaz; Israfil Kucuk; Mohammed Maniruzzaman; Ming-Wei Chang; Zeeshan Ahmad (Pharmaceutical Research, 2021)

Foliar Potassium-Induced Regulations in Glycine Betaine and Malondialdehyde Were Associated with Grain Yield of Heat-Stressed Bread Wheat (Triticum aestivum L.) - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Haroon Zaman Khan; Abdul Shakoor (Journal of Soil Science and Plant Nutrition, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

First report of Fusarium equiseti causing stem rot disease of grape (Vitis vinifera L.) in Afghanistan - Nasir Ahmed Rajput; Bakhat Zaman; Chao Huo; JiFen Cao; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Babar Khan; Owais Iqbal; Zhijian Zhao (Journal of Plant Pathology, 2020)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nexus between natural and technical disaster shocks, resource depletion and growth-specific factors: evidence from quantile regression - Waseem Akhter; Khalid Zaman; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro (Natural Hazards, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Impact of average temperature, energy demand, sectoral value added, and population growth on water resource quality and mortality rate: it is time to stop waiting around - Hafiza Samina Tehreem; Muhammad Khalid Anser; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

Social and administrative issues related to the COVID-19 pandemic in Pakistan: better late than never - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Xuan Hinh Vo; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Theranostic applications of smart nanomedicines for tumor-targeted chemotherapy: a review - Ajkia Zaman Juthi; Md Aquib; Muhammad Asim Farooq; Sana Ghayas; Farah Khalid; George Frimpong Boafo; Dickson Pius Wande; Daulat Haleem Khan; Tasnim Zaman Bithi; Rohit Bavi; Bo Wang (Environmental Chemistry Letters, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

Evolutionarily conserved and testis-specific gene, 4930524B15Rik, is not essential for mouse spermatogenesis and fertility - Ranjha Khan; Jingwei Ye; Ayesha Yousaf; Wasim Shah; Ayesha Aftab; Basit Shah; Qamar Zaman; Muhammad Zubair; Qinghua Shi; Xiaohua Jiang (Molecular Biology Reports, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

Achieving environmental sustainability through information technology: “Digital Pakistan” initiative for green development - Hassan Ahmad Nizam; Khalid Zaman; Khan Burhan Khan; Rubeena Batool; Muhammad Adnan Khurshid; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2020)

Core Competencies for Undergraduates in Bioengineering and Biomedical Engineering: Findings, Consequences, and Recommendations - John A. White; Donald P. Gaver; Robert J. Butera; Bernard Choi; Mary J. Dunlop; K. Jane Grande-Allen; Anna Grosberg; Robert W. Hitchcock; Aileen Y. Huang-Saad; Miiri Kotche; Aaron M. Kyle; Amy L. Lerner; et al. (Annals of Biomedical Engineering, 2020)

International tourism, social distribution, and environmental Kuznets curve: evidence from a panel of G-7 countries - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Measuring the ecological footprint of inbound and outbound tourists: evidence from a panel of 35 countries - Muhammad Imran Qureshi; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry; Alamzeb Aamir; Nik Hasnaa Nik Mahmood; Amran Md. Rasli; Khalid Zaman (Clean Technologies and Environmental Policy, 2019)

Dynamic linkages between tourism, energy, environment, and economic growth: evidence from top 10 tourism-induced countries - Kanwal Shaheen; Khalid Zaman; Rubeena Batool; Muhammad Adnan Khurshid; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Economics of death and dying: a critical evaluation of environmental damages and healthcare reforms across the globe - Rubeena Batool; Khalid Zaman; Muhammad Adnan Khurshid; Salman Masood Sheikh; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Saudi Arabia-China-Pakistan Economic Corridor: intergovernmental green initiatives - Asma Naz; Khalid Zaman; Sheikh Usman Yousaf; Abdelmohsen A. Nassani; Abdullah Mohammed Aldakhil; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

Cadmium induces GAPDH- and- MDH mediated delayed cell aging and dysfunction in Candida tropicalis 3Aer - Zaman Khan; Muhammad Atif Nisar; Saima Muzammil; Saima Zafar; Inga Zerr; Abdul Rehman (Environmental Monitoring and Assessment, 2019)

Access to clean technologies, energy, finance, and food: environmental sustainability agenda and its implications on Sub-Saharan African countries - Sanil S. Hishan; Sasmoko; Aqeel Khan; Jamilah Ahmad; Zainudin Bin Hassan; Khalid Zaman; Muhammad Imran Qureshi (Environmental Science and Pollution Research, 2019)

Natural disasters and Malaysian economic growth: policy reforms for disasters management - Muhammad Imran Qureshi; Rosman Md. Yusoff; Sanil S. Hishan; ASA Ferdous Alam; Khalid Zaman; Amran Md. Rasli (Environmental Science and Pollution Research, 2019)

Socio-economic and environmental factors influenced the United Nations healthcare sustainable agenda: evidence from a panel of selected Asian and African countries - Hummera Saleem; Wen Jiandong; Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Aqeel Khan; Zainudin Bin Hassan; Mohd Rustam Mohd Rameli (Environmental Science and Pollution Research, 2019)

Evaluation of SWAT Model performance on glaciated and non-glaciated subbasins of Nam Co Lake, Southern Tibetan Plateau, China - Muhammad Adnan; Shi-change Kang; Guo-shuai Zhang; Muhammad Naveed Anjum; Muhammad Zaman; Yu-qing Zhang (Journal of Mountain Science, 2019)

Inhibition of Melanosis, Microbial and Quality Changes of White Shrimp ( Penaues vannameii ) via Effect of Key Lime Juice and Vacuum Packaging at 2 ± 1ºC - Selvi Velu; Chong Cheong Yew; Muhammad Zukhrufuz Zaman; Fatimah Abu Bakar (Journal of Aquatic Food Product Technology, 2019)

Universal mitochondrial 16s rRNA biomarker for mini-barcode to identify fish species in Malaysian fish products - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Zaira Zaman Chowdhury; Sharmin Sultana; Mohd Rafie Johan; Abdul Rohman; Yuny Erwanto; Md. Eaqub Ali (Food Additives & Contaminants: Part A, 2019)

Management of green transportation: an evidence-based approach - Bilal Shouket; Khalid Zaman; Abdelmohsen A. Nassani; Abdullah Mohammed Aldakhil; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Moderating and mediating role of renewable energy consumption, FDI inflows, and economic growth on carbon dioxide emissions: evidence from robust least square estimator - Saiqa Naz; Rashida Sultan; Khalid Zaman; Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2019)

Food-beverage-tobacco consumption, smoking prevalence, and high-technology exports influenced healthcare sustainability agenda across the globe - Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2018)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

Isolation and characterization of chromium(VI)-reducing bacteria from tannery effluents and solid wastes - Mohammad Mahbub Kabir; Abu Naieum Muhammad Fakhruddin; Muhammed Alamgir Zaman Chowdhury; Md. Kamruzzaman Pramanik; Zeenath Fardous (World Journal of Microbiology and Biotechnology, 2018)

Water quality assessment of Ramser site, Indus Delta, Sindh, Pakistan - Muhammad Yar Khuhawar; Rafi O. Zaman Brohi; Taj Muhammad Jahangir; Muhammad Farooque Lanjwani (Environmental Monitoring and Assessment, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Thiolation of arabinoxylan and its application in the fabrication of controlled release mucoadhesive oral films - Muhammad Hanif; Muhammad Zaman (DARU Journal of Pharmaceutical Sciences, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Maximizing maize quality, productivity and profitability through a combined use of compost and nitrogen fertilizer in a semi-arid environment in Pakistan - Shahid Iqbal; Christian Thierfelder; Haroon Zaman Khan; Hafiz Muhammad Rashad Javeed; Muhammad Arif; Muhammad Shehzad (Nutrient Cycling in Agroecosystems, 2017)

Tourism in Austria: biodiversity, environmental sustainability, and growth issues - Muhammad Asad Saleem Malik; Syed Asim Shah; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Protein profiling analysis of Gossypium hirsutum (Malvales: Malvaceae) leaves infested by cotton whitefly Bemisia tabaci (Homoptera: Aleyrodidae) - Muhammad Ibrahim; Sumaira Yasmeen; Ghanva Zaman; Li Bin; Fahad Al-Qurainy; Habib-ur-Rehman Athar; Kausar Hussain Shah; Muhammad Khurshid; Muhammad Ashraf (Applied Entomology and Zoology, 2016)

Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Muhammad Imran Qureshi; Usama Awan; Zeeshan Arshad; Amran Md. Rasli; Khalid Zaman; Faisal Khan (Natural Hazards, 2016)

Environment and air pollution like gun and bullet for low-income countries: war for better health and wealth - Xiang Zou; Muhammad Azam; Talat Islam; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Causal nexus between energy consumption and carbon dioxide emission for Malaysia using maximum entropy bootstrap approach - Sehrish Gul; Xiang Zou; Che Hashim Hassan; Muhammad Azam; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Safe use of Cry genes in genetically modified crops - M. Rahman; Muhammad Zaman; Tayyaba Shaheen; Samra Irem; Yusuf Zafar (Environmental Chemistry Letters, 2015)

The battle of health with environmental evils of Asian countries: promises to keep - Muhammad Imran Qureshi; Noor Ullah Khan; Amran Md. Rasli; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Does energy consumption contribute to environmental pollutants? evidence from SAARC countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Danish Irfan; Muhammad Mushtaq Khan (Environmental Science and Pollution Research, 2014)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

Decoupling Directed and Passive Motion in Dynamic Systems: Particle Tracking Microrheology of Sputum - Erika J. Fong; Yasha Sharma; Brian Fallica; Dylan B. Tierney; Sarah M. Fortune; Muhammad H. Zaman (Annals of Biomedical Engineering, 2013)

Metal pollution and ecological risk assessment in marine sediments of Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2013)

Synthesis, characterization and in vitro hydrolysis studies of ester and amide prodrugs of dexibuprofen - Zaman Ashraf; Muhammad Imran; Shahid Amin (Medicinal Chemistry Research, 2012)

Computational Model for Migration of a Cell Cluster in Three-Dimensional Matrices - Diego A. Vargas; Muhammad H. Zaman (Annals of Biomedical Engineering, 2011)

Computational Study of Proteolysis-Driven Single Cell Migration in a Three-Dimensional Matrix - Dewi Harjanto; Muhammad H. Zaman (Annals of Biomedical Engineering, 2010)

Computational Model Provides Insight into the Distinct Responses of Neurons to Chemical and Topographical Cues - Leandro Forciniti; Christine E. Schmidt; Muhammad H. Zaman (Annals of Biomedical Engineering, 2009)

Understanding Effects of Matrix Protease and Matrix Organization on Directional Persistence and Translational Speed in Three-Dimensional Cell Migration - Muhammad H. Zaman; Paul Matsudaira; Douglas A. Lauffenburger (Annals of Biomedical Engineering, 2006)